EDUKASI TEOLOGI DALAM KELUARGA KRISTEN SEBAGAI PONDASI PREVENTIF RADIKALISME - Ibelala Gea (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2021)
One of the factors in the emergence of radicalism is the misinterpretation of the Scriptures and the weak theological education in the family. Parents as the primary and first educators in fact tend to leave their assignments to other parties who do not necessarily educate their children properly. The impact of this bad and incorrect theological education tends to form a mindset of exclusivism and rejecting inclusivism that creates intolerant people, considers all who do not have the same opinion and belief as the address of violence that must be eradicated. The family, both in the Old and New Testament times, in this case the parents, has the obligation and responsibility to educate children to understand the essence of God properly and correctly to His people. This article uses the mix methods method by collecting data on 30 (thirty) members of the Whatsapp Group STM Marsiurupan Sipoholon District which aims to describe 5 (five) theological educational content in Christian families as a preventive foundation for radicalism, especially radicalism in the name of religion in a descriptive qualitative method. 5 (five) theological educational contents are (1) Educating children to understand the Scriptures properly and correctly; (2) Understanding the essence of One God; (3) Understanding the essence of God as a savior, (4) Understanding the essence of God as a preserver; and (5) Understanding the essence of God as loving and compassionate.